Hydrophobic fluorinated TiO2-ZrO2 as catalyst in epoxidation of 1-octene with aqueous hydrogen peroxide - Nur , Hadi; Ng, Yun Hau; Misnon, Izan Izwan; Hamdan, Halimaton; Muhid, Mohd Nazlan Mohd (Elsevier B.V., 2006)

(untitled)
A new heterogeneous oxidation catalyst was prepared by impregnation of TiO2 from titanium(IV)tetra-2-propoxide on the surface of ZrO2. The surfaces of TiO2-ZrO2 particles were then modified by the fluorination of ammonium hexafluorosilicate and followed by alkylsilylation of n-octadecyltrichlorosilane (OTS). The resulting catalysts were characterized by X-ray diffraction (XRD), nitrogen adsorption isotherm, UV-Vis Diffuse Reflectance (UV-Vis DR), and Energy Dispersive X-Ray Analysis (EDAX) techniques. The catalytic potential of catalysts for oxidation reactions has been verified in the liquid phase epoxidation of 1-octene to 1,2-epoxyoctane with aqueous hydrogen peroxide. It is demonstrated that the fluorination and alkylsilylation enhance the catalytic activity of TiO2-ZrO2. A high catalytic activity of the modified TiO2-ZrO2 was related to the modification of the local environment of titanium active site and increasing the hydrophobicity of catalyst particles by fluorination and alkylsilylation.